Evaluasi Pengendalian Internal Terhadap Proses Pemberian Kredit Mikro Pada Bank X - Putri, Kezya Aninditha; Nugraha, Adri Putra (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
The objective of this research is to identify whether the internal control applied by Bank X has been in conformance with the COSO. The data of this qualitative descriptive research was harvested from observations, interviews, and documentation. The research site is the Tangerang Ahmad Yani branch Office of PT Bank X (Persero), which is located in Tangerang of Banten. This study finds that the bank has sufficient control over its approval processes for microloans. However, poor documentation of its activities and sub-optimal supervision have hindered the quality of its internal control.